PENGEMBANGAN MODEL PROJECT-BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BAHASA INGGRIS SISWA PONPES MODERN DI MALANG RAYA - Suhartatik, Suhartatik; Adi, Adi (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2014)
English is taught in Modern Islamic Boarding SchoolÂ  as one ofÂ  language competences must be mastered by the studentsÂ  beside Arabic. The teachers findÂ  difficulties to implementÂ  learning models that make the students to be activeÂ  andÂ  the students need others learning variation.Â  Research and Development (R D) design is used in thisÂ  researchÂ  that aimÂ  to produce the development of â€œProject Based-Learning Modelâ€ plus VCD to improve the Students' English Ability of Modern Islamic Boarding School at Malang Area. The model of development is adopted byÂ  Borg and Gall ModelÂ  starting from collecting information,Â  development of initial product, 1st expert validation, 1stÂ  product revision, 2nd expert validation, 2nd product revision, tryout, and final product. The Expertsâ€™ English Material validation conclude that formulation of learning objective, content, material selection for development of â€œProject Based-Learning Modelâ€ have got category ofÂ  Excellent. The validation of the Expert of MediaÂ  conclude that final product of VCD have been appropriatedÂ  with the aspectsÂ  ofÂ  learning media that are feasible to be applied.